The Influence Of Capital Structure, Company Size, And Business Risk On Profitability In Palm Plantation Companies Listed On The Indonesian Stock Exchange Year 2019-2023 - Jusmiati Jusmiati; Eddy Irsan Siregar; Riyanti Riyanti (UNIVED Press, 2025)
This research aims to analyze and examine the influence of capital structure on profitability in palm oil companies listed on the BEI in 2019-2023, Analyze and examine the influence of company size on profitability in palm oil companies listed on the BEI in 2019-2023, Analyze and examine the influence of business risk on palm oil companies registered on the IDX in 2019-2023 and Analyze the validity test, reliability of the questionnaire and examine the influence of capital structure, company size and business risk in influencing profitability in palm oil companies registered on the IDX in 2019-2023.This research is quantitative research. The analytical method used is multiple regression analysis. The population in this research is all palm oil companies registered on the IDX for the 2019-2023 period. Based on the purposive sampling method, 13 companies were obtained as samples that met the sampling criteria. The data analysis technique used was statistical analysis with the Eviews 9 computer program to analyze and test research data. The results of this research show that Capital Structure has a negative and insignificant effect on the Company's profitability, Company Size has a positive and significant effect on the Company's profitability and Business Risk has a positive and significant effect on the Company's profitability. Therefore, in accordance with hypothesis 4 which states that of the variables used in this research, the variables that have a significant influence are the variables Company Size (Size), Business Risk (Brisk). Meanwhile, the Capital Structure (DER) variable has no effect on profitability in oil palm plantation companies listed on the Indonesia Stock Exchange.